The emotional and relational impact of starting kindergarten for non-native speaking children: a case study of a three- year-old child - Toth, Angelika (Gyermeknevelés Tudományos Folyóirat, 2022)
This paper presents a case study and some results of a longitudinal study conducted from 2013 to 2018 in preschools in Hungary and Switzerland. This study has been prepared as part of the author’s PhD research at the University of Geneva (Toth, 2018). The objective of this research was to reveal the relational and emotional experience of entering kindergarten/ school for non-native speaking children, i.e., children who do not speak and understand the language spoken at kindergarten or school. (In this case study, the chosen child did not speak Hungarian when she started kindergarten). To capture the complexity of the emotional experience, a special observation form has been chosen called the Esther Bick method (Bick, 1964; Franchi & Toth, 2014), which has been developed in the training of child psychotherapists in the Tavistock Clinic in London. Through the unconscious, projective, and transferential movements captured by the observations and completed by other mainly qualitative tools, I could reveal the internal movements that go through the children and approach their fears and their anxieties.